Poverty, growth, and income distribution in Kenya: A SAM perspective - Gakuru, Wachira Rhoda; Mathenga, Naomi Muthoni (International Food Policy Research Institute, 2012)
This study seeks to highlight the level of income inequality in Kenya and its implications on various poverty reduction policies. The 2003 Kenya SAM is used to develop a multiplier simulation model which tracks the linkages among demand-driven shocks and economic growth, income generation, and income distribution for different economic groups.